Implications of Palm Kernel Shell-Filled Plastic Bottles on the Structural Behavior of Concrete Slab - Donald Kwabena Dadzie; A. K. Kaliluthin (Civil Engineering Journal, 2023)
The implications of palm kernel shell (PKS)-filled plastic bottles on the structural behaviour of concrete slabs were carried out by comparing the flexural performance of conventional solid concrete slabs to concrete slabs incorporated with plastic bottles filled with palm kernel shells and placed vertically, horizontally, and diagonally at the neutral axis of the slab as per Bubble Deck Slab technology. One-way slab specimens of size 700 × 300 × 150 mm thick were produced and subjected to a four-point flexural load test. Findings from the study indicated that: (1) The PKS-filled bottle slabs deflected more than the conventional solid slab, hence making them more flexible than the conventional slabs and, as such, giving the occupants enough time to evacuate. (2) The flexural strengths of the PKS-filled bottle slabs exceeded those of conventional slabs by 18.3% and 10.9%, respectively, for five and ten percentages of the volume of slab concrete occupied. (3) The condition of the PKS, either dry or saturated, coupled with the bottle arrangement (either vertical, horizontal, or diagonal), does not, however, cause any significant change to the performance of the PKS filled bottle slabs in terms of load carrying capacity, deflection, and strength. Doi: 10.28991/CEJ-2023-09-03-016 Full Text: PDF